Micafungin Effectiveness in Treating Pediatric Patients with Proven Candidemia - Kamile Ötiken Arıkan; Oğuzhan Kalkanlı; Şebnem Çalkavur; Şeyma Akkuş; Mustafa Çolak; Elif Böncüoğlu; Elif Kıymet; Aybuke Akaslan Kara; Hasan Agın; Nuri Bayram; İlker Devrim (Galenos Yayinevi, 2022)
Aim:Micafungin is one of three currently available echinocandin for the treatment of candidiasis and candidemia. We aimed to discuss the effectiveness of micafungin and any possible side effects in the treatment of proven candidemia in children.Materials and Methods:In this study, children who were treated with micafungin for proven candidemia between May, 2017 and October, 2019 were included. The time to achieve negative culture, liver and renal functions as well as blood counts were recorded using the hospital data system.Results:Forty-five patients (52.3%) who received micafungin for proven candidemia were included in this study. The median age of the children who received micafungin due to invasive candidiasis (IC) was 4 months (range: 12 days to 216 months). Of these 45 IC patients, 10 (22.2%) were neonates, 19 (42.2%) were infants, 11 (24.4%) were between 1 and 5 years old, and 5 (11.1%) were between 10-18 years old. The median duration of micafungin treatment to culture negativity for C. albicans related candidemia episodes was shorter (6 days, 1-26 days) than non-albicans Candida spp. related candidemia episodes (7 days, 1-35 days) (p=0.10). Culture negativity could not be achieved at the end of the 14th day of micafungin treatment in 15 of the 45 (33.3%) candidemia episodes. The most commonly isolated Candida spp. in patients with treatment failure was C. parapsilosis (n=6), followed by C. albicans (n=5), C. guilliermondii (n=1), C. tropicalis (n=2) and C. tropicalis and C. guilliermondii co-infection (n=1) respectively. None of the patients developed side effects due to micafungin treatment.Conclusion:Micafungin was found to be safe and effective for the treatment of culture proven candidemia in pediatric patients, including neonates.